Prediction of Addiction Readiness in Cancer Patients Based on the Perception of Social Support with the Mediation of Pain Self-Efficacy and Pain Acceptance - Sarah Behzad; Yahya Yarahmadi; Farshad Bahari; Hamzeh Ahmadian (طب انتظامی, 2023)
Aims: Cancer pain creates negative thoughts and beliefs in patients, which can affect the level of functioning and pain tolerance in these patients. In recent decades, the use of drugs for pain relief in cancer patients has increased dramatically. The present study was conducted with the aim of investigating the mediating role of pain acceptance and pain self-efficacy in the relationship between the perception of social support and readiness for addiction. Materials and Methods: The statistical population of this descriptive-correlation study was men and women with cancer in Arak city in 2020-2021. A total of 201 cancer patients referred to Arak hospitals were selected by available sampling method (97 women and 104 men). Perceived Social Support Questionnaire of Zimet et al. (1988), Pain Self-Efficacy Questionnaire of Nicholas (1980), Chronic Pain Questionnaire of Vowels et al. (2004) and Addiction Readiness Questionnaire by Wade and Butcher (1992) were completed by all the samples. For data analysis, path analysis method was used using SPSS 25 and Amos 24 software. Findings: Out of 215 participants, 14 were excluded from the analysis due to incomplete completion of the questionnaires, and the final analysis was performed on 201 people. Of these, 104 were men (51.75%), and 97 were women (48.25%). The average age of the participants in the research was 53.46±10.38 years, and 34.82% had a middle school diploma (70 people), 24.37% had a high school diploma (49 people), 30.84% had a bachelor's degree (62 people), and 9.95% had a master's degree or higher (20 people). Nineteen people (9.45%) were single, and 165 (82.08%) were married. Thirty-one (15.4%) of the participants had breast cancer, 29 (14.4%) had prostate cancer, 36 (17.9%) had stomach cancer, 33 (16.4%) had colon cancer, 26 people (12.9%) had bladder cancer, 25 people (12.4%) had skin cancer, nine people (4.5%) had uterine cancer, and 12 people (6.0%) had thyroid cancer. The value of kurtosis and skewness of the variables was in the range of -2 to +2, so the data had a normal distribution and the default of data analysis was followed (Table 1). There was a negative and significant correlation between the perception of social support and potential for addiction (r=-0.389). Also, there is a positive and significant relationship between the perception of social support and pain acceptance (r=0.486), a positive and significant correlation between the perception of social support and pain self-efficacy (r=0.462), and a negative and significant correlation between pain acceptance and potential for addiction (r=-0.511). Moreover, there was a negative and significant relationship between pain self-efficacy and potential for addiction (r=-0.414). After descriptive data analysis, path analysis defaults were checked and confirmed. The multicollinearity of the variables was investigated using the tolerance statistic and variance inflation factor, and the results showed no multicollinearity between the variables. Path analysis was used to examine the relationship between the variables of perception of social support, pain acceptance, pain self-efficacy, and potential for addiction. Figure 1 shows the path analysis diagram of the final model, and Table 3 shows the fit indices of the final model in the target sample. The fit indices of the final model include the chi-square index (X²/Df=2.94), comparative fit index (CFI=0.99), incremental fit index (IFI=0.99), Tucker-Lewis fit index (TLI=0.93), and the root mean square deviation of approximation (RMSEA=0.09) indicated the optimal fit of the final model. The results of the direct effect of social support perception on pain acceptance, social support perception on pain self-efficacy, pain acceptance on addiction, and pain self-efficacy on addiction and the standard indirect coefficient of social support perception on addiction with the mediating role of pain acceptance and pain self-efficacy was equal to -0.30 (Table 4). The result of the Sobel test for the significance of the mediating variable of pain acceptance was equal to 3.40 and for the variable of pain efficiency was equal to 2.39. Since the z-value was greater than 1.96, the significance of the influence of mediating variables was confirmed. Conclusion: Strengthening the social support network of individuals, along with developing a sense of self-efficacy and acceptance of uncontrollable aspects, can be considered as preventive treatment goals and plans for patients' tendency to use drugs for pain relief. CLINICAL & PRACTICAL TIPS in POLICE MEDICINE By providing a platform to increase the social network of individuals and by emphasizing holding training courses that are fundamental factors in the formation of an independent and coherent identity when facing life-threatening diseases, psychologists and counselors of military institutions can promote patients’ acceptance and self-efficacy in order to increase the mental health of police forces in the society. Acknowledgments: We appreciate all the patients who participated in this study. CONFLICT of INTEREST: The authors stated that there is no conflict of interest in the present study. AUTHORS CONTRIBUTION: First author, ideation, study design, data collection, data analysis; second author, study design, data collection, data analysis; third and fourth authors, study design and data analysis. All the authors participated in the initial writing of the article and its revision, and all accept the responsibility for the accuracy and correctness of the article's contents with the final approval of this article. FUNDING SOURCES This research had no financial support.